Significance of B-catenin Immunohistochemical Expression in Colorectal Carcinoma - Zilan Aziz Abdulrahman; Ava Tahir Ismael; Jalal Ali Jalal; Wahda Muhammed Taib Alnuaimy (Advanced Medical Journal)
Background and objectives: Colorectal cancer is the third leading cause of cancer death worldwide and B- catenin has a role in the development of colorectal cancer. The objective of this study was to investigate the B-catenin expression of colorectal carcinoma and assess its correlation with some clinicopathological parameters in Erbil, Kurdistan of Iraq.